Acute kidney injury induced by beta-lactam antibiotics in children: A scoping review - Tania, Astalitha Lorel; Alya Ayu Tazkia (Universitas Muhammadiyah Surabaya, 2024)
Antibiotics are the agents that cause Acute Kidney Injuries (AKI) in children. A recent study has shown the incidence of nephrotoxicity by antibiotics reaches 16% in children. Beta-lactam types are not widely known for their nephrotoxic effect. This study aims to examine beta-lactam antibiotics' role in inducing children's renal failure. This search for a scoping review on the effect of beta-lactam antibiotics in children was carried out in December-January 2022-2023. We used some search engines with the year of publication 2012-2022 then extracted. The keyword combinations used are: “beta-lactams” OR “β-lactams” AND “acute renal failure” OR “acute renal injury” OR “nephrotoxic” OR “nephrotoxicity” AND “children” OR “pediatric” OR “neonate” NOT “adult”. Studies were excluded if the: (i) adult; (ii) were a review, systematic review, or meta-analysis; (iii) written in a language other than English; (iv) not available in full text; (v) have kidney disease before (vi) in vitro or in vivo. The article selection process was based on PRISMA-ScR. From 4032 articles that met the search criteria, 3 studies met the inclusion criteria. The result shows that beta-lactam increases the risk of acute renal injury in children. This review emphasizes the importance of choosing kidney-safe antibiotics for children.